The Double-Edged Sword of Immunosuppressive Therapy in Kidney Transplantation: A Rare Case Report of Pulmonary Mucormycosis Post-Transplant and Literature Review - Zhang, Hengcheng; Wang, Ke; Chen, Hao; Sun, Li; Wang, Zijie; Fei, Shuang; Tan, Ruoyun; Gu, Min (Frontiers in Medicine, 2020)
Immunosuppressive therapy is improving the graft survival of kidney transplant recipients and increasing the potential risk of infection. Pulmonary Mucormycosis is a rare postoperative infection complication charactered with rapid deterioration and high mortality. In this case, a 33-year-old patient underwent kidney transplantation with regular immunosuppressive therapy. On 38 days posttransplant pulmonary patchy shadows can be seen in the radiological examination and rounded into large cavity formation with splenic rupture 25 days later. The diagnosis of mucormycosis was confirmed by lung biopsy and spleen histopathology. This case is a reminder that early diagnosis is imperative, meanwhile, rational antifungal therapy, timely elimination of immunosuppressants and alternative abandoning the graft should be prudently assessed in the treatment of mucormycosis.